Selection of the Disc Brake Material Using Pin on Disc Apparatus: A Review - Singh, Harvinder (Asian Review of Mechanical Engineering, 2017)
An automobile brake disc is a device used for slowing or stopping the motion of a wheel while it runs at certain speed. The mostly used brake disc material is cast iron which consumes much fuel due to high specific gravity. The main aim is to develop the material selection and select optimum material for the application of brake disc system for better working. The paper describes the tribological behavior of the conventional materials i.e. Gray cast Iron, Structural steel, Aluminum and High speed steel (HSS). In this paper to check major tribiological parameters for these four materials and try to suggest better new material compared to conventional existing material. After Test on wear machine we find the best suitable material for disc brake applications because of its low wear rate, low frictional force, low coefficient of friction, low cost, better mechanical properties than other.